ANALISIS RENJA (RENCANA KERJA) KEGIATAN PERANGKAT DAERAH PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BULUNGAN - LUKITA UTAMI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to analyze the Work Plan (Renja) at the Education and Culture Office of Bulungan Regency in 2022. This research is a type of descriptive research with a qualitative method approach. The subject of this research is the process of implementing the Work Plan (Renja) at the Education and Culture Office of Bulungan Regency, the research location is at the office of the Education and Culture Office of Bulungan Regency, Jl. Colonel Soetadji, Tanjung Selor District, Bulungan Regency, North Kalimantan Province. The research time is 1 (one) month, namely January 1 2023 to February 1 2023. Data collection techniques use observation, interviews and documentation. The types of data used are primary data and secondary data. Primary data obtained from interviews. The informants in this research interview were the Head of the Education and Culture Office as the Budget User, the Secretary of the Education and Culture Office, the Activity Technical Implementation Officer (PPTK), the planning implementing staff. Secondary data is in the form of documents owned by the Education and Culture Office of Bulungan Regency. Based on the results of the research that has been carried out, it can be concluded that the implementation of the Work Plan (Renja) preparation at the Education and Culture Office of Bulungan Regency in 2022 has gone well according to the applicable provisions and guidelines. Planning Document Suggestions for program proposals and community activities proposed in the Village and District Level Development Planning Meetings (Musrenbang) that have not been accommodated in the Work Plan of the Education and Culture Office of Bulungan district are proposed through the direct aspirations of Members of the Regional People's Legislative Council (DPRD) through the main ideas Member of the Regional People's Representative Council (DPRD). ABSTRAKPenelitian ini bertujuan untuk menganalisis Rencana Kerja (Renja) pada Dinas Pendidikan dan Kebudayaan Kabupaten Bulungan tahun 2022. Penelitian ini dengan pendekatan metode kualitatif. Subjek penelitian ini adalah proses pelaksanaan penyusunan Rencana Kerja(Renja) pada Dinas Pendidikan dan Kebudayaan Kabupaten Bulungan, tempat penelitian di kantor Dinas Pendidikan dan Kebudayaan Kabupaten Bulungan, Jl.Kolonel Soetadji Kecamatan Tanjung Selor,Kabupaten Bulungan, Provinsi Kalimantan Utara. Waktu penelitian selama 1 (satu) bulan yaitu tanggal 1 Januari 2023 sampai tanggal 1 Februari 2023.Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi.Jenis data yang digunakan adalah data primer dan data sekunder. Data primer diperoleh dari hasil wawancara Adapun narasumber dalam wawancara penelitian ini adalah Kepala Dinas Pendidikan dan Kebudayaan selaku Pengguna Anggaran, Sekretaris Dinas Pendidikan dan Kebudayaan, Pejabat Pelaksana Teknis Kegiatan (PPTK), staf pelaksana perencanaan. Data Sekunder adalah berupa dokumen yang dimiliki Dinas Pendidikan dan Kebudayaan Kabupaten Bulungan. Berdasarkan hasil penelitian yang telah dilakukan dapat diperoleh kesimpulan bahwa pelaksanaan penyusunan Rencana Kerja (Renja) pada Dinas Pendidikan dan Kebudayaan Kabupaten Bulungan tahun 2022 telah berjalan dengan baik sesuai ketentuan dan pedoman yang berlaku. Dokumen Perencanaan Saran untuk usulan program dan kegiatan masyarakat yang diusulkan dalam Musyawarah Rencana Pembangunan (Musrenbang) Tingkat Desa dan Kecamatan yang belum diakomodir dalam Renja Dinas pendidikan dan Kebudayaan kabupaten Bulungan diusulkan melalui aspirasi langsung Anggota Dewan Perwakilan Rakyat Daerah (DPRD) melalui pkok-pokok pikiran Anggota Dewan Perwakilan Rakyat Daerah (DPRD).